Learning dashboards at scale: early warning and overall first year experience - Broos, Tom; Pinxten, Maarten; Delporte, Margaux; Verbert, Katrien; De Laet, Tinne (Assessment and evaluation in higher education, 2020)
In this study, we present a case study involving two self-service dashboards providing feedback on learning and study skills and on academic achievement. These dashboards were offered to first-year university students in several study programmes in Flanders, Belgium. Data for this study were collected using usage tracking (N = 2875) and a survey taken at the beginning of the second year before (N = 484) and after (N = 538) the introduction of the dashboards. We found that early dashboard usage is related to academic achievement later in the academic year and that students' review of the feedback received in the first year improved. Although these results are modest in comparison to how high the bar is sometimes set for learning analytics applications, we argue that low-cost deployments of self-service dashboards are an interesting approach to start building experience with similar tools and to start paving the way for future developments.